The relationship between lecture attendance and academic performance in an undergraduate psychology class - Thactcher, A; Fridjhon, P; Cockcroft, K (South African Journal of Psychology, 2007)
This article reports on a preliminary investigation into the impact of non-attendance at lectures on the performance of students in a second-year psychology class. Results suggest that the frequency of lecture attendance is significantly, but moderately, related to better academic performance and that 'always' attending lectures is the best indicator of academic performance. These results are discussed in relation to understanding lecture non-attendance and improving academic performance
Keywords: Academic performance; Lecture attendance; Teaching psychology; Undergraduate psychology classes